In vivo evaluation of the sealing ability of two endodontic sealers in root canals exposed to the oral environment for 45 and 90 days (Journal of Applied Oral Science, 2006)
This in vivo study evaluated the sealing ability of a resin-based sealer (AH Plus) and a zinc oxide-eugenol sealer (Endofill) in dogs' teeth, exposed to the oral environment for 45 and 90 days. Forty eight lower incisors from 8 dogs were endodonticaly treated. A stratified randomization determined the sealer use in each root canal. All canals were filled using the lateral condensation technique. The excess filling material at the cervical portion of the root canal was sectioned, leaving a 10-mm obturation length inside the canal. Teeth were provisionally sealed with glass ionomer cement for 24 h and the canals were exposed to the oral environment for either 45 or 90 days. Therefore, the experimental groups were as follows: A45- AH Plus for 45 days; A90- AH Plus for 90 days; E45- Endofill for 45 days; and E90- Endofill for 90 days (n=12). After the experimental period, the dogs were killed and the lower jaw was removed. The incisors were extracted and the roots were covered with two coats of nail varnish. The teeth were immersed in India ink for 96 h and submitted to diaphanization. Dye leakage (in mm) was measured using stereomicroscopy (10x magnification). The results were statistically analyzed using two-way ANOVA and Tukey test for multiple comparisons (á = 0.05). Group E90 (2.03±0.94) showed significantly higher mean leakage value than all other groups (p